Constructing and Deconstructing Teen Pregnancy as a Social Problem - Neiterman, Elena (Qualitative Sociology Review, 2012)
The purpose of this paper is to examine teenage pregnancy as a social problem using social constructionist perspective. Analyzing qualitative interviews with 11 young mothers and relying on the media analysis of popular North American newspapers and magazines, I examine claims-making activity around the definition of teenage pregnancy as a social problem. I start this paper, situating my arguments in the social constructionist literature on social problems. In the second part of this paper I review the literature on teen pregnancy and identify three major themes that dominate academic and public discourse on pregnancy as a social problem. After describing the methodological approach I took to conduct this study, I move on to present my findings. I demonstrate that in negotiating their mothering skills, young teenage mothers construct their claims about pregnancy, parenthood and their future vis-à-vis the dominant public discourse on teen pregnancy. They reconstruct their pregnancy and mothering as non-deviant, claim their status as mature and responsible mothers and challenge the importance of biological age as a predictor of successful mothering. I summarize this paper suggesting that these young women’s narratives should be considered the claims-making activity of a marginalized population of young mothers who are rarely heard in public, yet they do challenge our assumptions about teen mothering and find their own way to resist the dominant discourse on teen pregnancy.